Sovereign Debt Distress and Corporate Spillover Impacts - Dailami, Mansoor (2012)
In much of the standard corporate finance literature in which sovereign debt is treated as a risk free asset, corporate bond prices are seen to depend on idiosyncratic risk factors specific to the issuing company, with public debt playing an indirect role to the extent that it affects the term structure of interest rates. In the corporate world, however, the ability of a borrower to access international capital markets and the terms according to which it can raise capital depend not only on its own creditworthiness, but also on the financial health of its home-country sovereign. In times of financial stress, when investors lose confidence in the government's ability to use public finances to stabilize the economy or provide a safety net for corporations in distress, markets' assessment of private credit risk takes on a completely different dynamic than during normal times, incorporating an additional risk premium to compensate investors for the potential consequences of sovereign default. Using a new database that covers nearly every emerging-market corporate and sovereign entity that has issued bonds on global markets between 1995 and 2009, this paper investigates the degree to which heightened sovereign default risk perceptions during times of market turmoil influence the determination of corporate bond yield spreads, controlling for specific bond attributes and common global risk factors. Econometric evidence presented confirms that investors' perceptions of sovereign debt problems translate into higher costs of capital for private corporate issuers, with the magnitude of such costs increasing at times when sovereign bonds trade at spreads exceeding a threshold of 1000 bps. The key policy recommendation emerging from the analysis relates to the need to improve sovereign creditworthiness in order to prevent a loss in investor confidence that could trigger a panicky sell-off in sovereign debt with adverse macroeconomic and fiscal consequences. Implications for future research point to the need to develop better models of corporate bond pricing and valuation, recognizing explicitly the role of sovereign credit risk.